(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
The forces that shaped the personality of Iranian cities included an understanding of nature, a precise feeling for climatic conditions. Changes in economic, social, as well as cultural conditions, also occurred very slowly and over long periods of time. Since the end of the 19th century social and economic conditions have been rapidly changing. In this period of time, the industrial model of Europe became the example for defining progress. These changes have been both negative and positive